The art of application performance testing - Molyneaux, Ian (O'Reilly Media, 2015)
A step-by-step approach to testing mission-critical applications for scalability and performance before they're deployed. this practical book explains the complete life cycle of the testing process, and demonstrates best practices to help programmers plan, gain approval for, coordinate, and conduct performance tests on their applications.